2019
DOI: 10.16916/aded.466685
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Altıncı Sınıf Öğrencilerinin Sözcük Düzeyinde Yazım Yanlışlarının İncelenmesi

Abstract: Bu araştırmanın amacı, ortaokul altıncı sınıf öğrencilerinin sözcük düzeyinde yazım yanlışlarının incelenmesidir. Araştırma, nitel araştırma yöntemlerinden doküman incelemesi yöntemiyle gerçekleştirilmiştir. Kolay ulaşılabilir durum örneklemesi kapsamında Yozgat ili Merkez ilçedeki bir devlet ortaokulunda altıncı sınıfta öğrenim gören 163 öğrenci ile çalışılmıştır. Öğrencilerin 85'i erkek, 78'i kızdır. Veriler 2018 yılı mayıs ayında toplanmıştır. Ortaokul altıncı sınıf öğrencilerine Türkçe derslerinde bir ders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
1
5
0
2
Order By: Relevance
“…Prior studies in the literature have assessed morphological valency errors of secondary school students in their written products as a of incoherency (Babayiğit, 2019;Bedirhanoğlu, 2010;Büyükikiz, 2009;Üstün, 2011;Yiğit, 2009). Among those studies, Üstün (2011) who evaluated written expressions of secondary school students having different socio-economic levels found that at least one secondary school student made a mistake in his/her written product in terms of incoherency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies in the literature have assessed morphological valency errors of secondary school students in their written products as a of incoherency (Babayiğit, 2019;Bedirhanoğlu, 2010;Büyükikiz, 2009;Üstün, 2011;Yiğit, 2009). Among those studies, Üstün (2011) who evaluated written expressions of secondary school students having different socio-economic levels found that at least one secondary school student made a mistake in his/her written product in terms of incoherency.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, morphological valency in Turkish teaching has been limited with the sub dimensions of incoherency and morphological valency errors of secondary school students in language use have been included in structural faults (Babayiğit, 2019;Bedirhanoğlu, 2010;Bozarslan, 2019;Büyükikiz, 2009;Üstün, 2011;Yiğit, 2009). Among those studies, Üstün (2011) determined that there were at least one incoherency in secondary school student having different socio-economic levels and this incoherency was related to syntax.…”
mentioning
confidence: 99%
“…Yazım hataları, literatürde iki farklı yolla sınıflandırılmaktadır. Türkçe yazım hatalarını ele alan çoğu çalışmanın da yer aldığı grup, yazım hatalarını, yüzeydeki temsil biçimlerine (Beers ve Beers, 1992;Babayiğit, 2019) göre sınıflandırmaktadır. Bu sınıflandırma, harf düşürme, harf değiştirme ve hece düşürmeyi içermektedir.…”
Section: Yazım Hatalarının Sınıflandırılmasıunclassified
“…Spelling errors in Turkish made by school-aged children have been mostly categorized in terms of whether phonemes or syllables are omitted, added or substituted (Erden, Kurdoğlu, and Uslu, 2002;Sönmez, Babür, and Haznedar, 2015;Babayiğit, 2019). In the current study, on the other hand, the spelling errors in Turkish are categorized with respect to possible cognitive factors behind these…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…Konunun bireyin hayatında sürekli gündemde olmasının, araştırmacıların bu konuya yönelmelerinde etkisi olduğu söylenebilir. Alanyazındaki çalışmalar incelendiğinde ilkokul (Akmugan, 2019;Alkan, 2007;Çetin, 2013;Yıldız & Ateş, 2010), ortaokul (Akbaba & Yalçın, 2016;Akkaya, 2013;Arıcı & Ungan, 2008;Avcı, 2006;Babayiğit, 2019;Bağcı, 2011;Ekinci-Çelikpazu, 2006;Karagül, 2010;Kırbaş, 2006;Kırbaş, 2010;Oğuz, 2012;Özcan & Yönez, 2018;Şişmanoğlu, 2009;Töremen, 2008;Uludağ, 2002;Yıldırım & Uludağ, 2016), lise (Acar, 2011;Erdem, 2007;Gedik, 2008;Özdemir, 2008;Soruklu, 2011), lisans (Arıcı, 2008;Bağcı, 2010;Bakır, 2010;Dumanlı-Kadızade, 2015;Kana & Gümüşkaya, 2018;Karabuğa, 2011;Lüle-Mert, 2015;Topuzkanamış, 2009) seviyesi gibi farklı kademelerde öğrenim gören öğrencilerin ve ana dili Türkçe olanların dışında yabancı dil olarak Türkçe öğrenen öğrencilerin (Aytan & Güney, 2015;Fidan, 2019) yazılı anlatımlarını noktalama işaretlerinin kullanımı/imla kuralları bakımından değerlendiren çalışmaların mevcut olduğu görülmektedir. Bunun yanında farklı öğrenim kademelerindeki bireylerin yazım ve noktalama kurallarını uygulama becerilerini karşılaştırmalı olarak inceleyen araştırmalara da (Batur, Erkek, Ertan-Özen & Ellialtı, 2017;…”
unclassified